2014
DOI: 10.1097/mjt.0b013e318274df35
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Toxicity and Sorafenib

Abstract: We report a case of a 55-year-old male with chronic hepatitis C virus infection and compensated liver disease treated with sorafenib for advanced hepatocarcinoma (Barcelona Clinic Liver Cancer stage C). At follow-up, the patient developed hypertension, which was well controlled with beta-blocker medication, and an aortic dilation detected by abdominal computerized tomography and echocardiography. There are some reports of the side effects of sorafenib on the cardiovascular system. The patient had no cardiac or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Accordingly, a case-report study published in 2014 showed that the patient treated with sorafenib developed hypertension and an aortic dilation detected by abdominal computerized tomography and echocardiography. Which was well controlled with β-blocker medication [ 12 ]. Also, in this observational, single-center study of 74 patients using either sorafenib or sunitinib, 33.8% had a cardiac event, 40.5% had ECG changes, 18% were symptomatic, and 9.4% of these patients were seriously compromised and required intensive care admission, so careful cardiovascular monitoring should be considered [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a case-report study published in 2014 showed that the patient treated with sorafenib developed hypertension and an aortic dilation detected by abdominal computerized tomography and echocardiography. Which was well controlled with β-blocker medication [ 12 ]. Also, in this observational, single-center study of 74 patients using either sorafenib or sunitinib, 33.8% had a cardiac event, 40.5% had ECG changes, 18% were symptomatic, and 9.4% of these patients were seriously compromised and required intensive care admission, so careful cardiovascular monitoring should be considered [ 13 ].…”
Section: Introductionmentioning
confidence: 99%